A Lie More Disastrous than the Truth: Asylum and the identification of trafficked women in the UK - Stepnitz, Abigail (Anti-Trafficking Review, 2012)
This article explores the impact that nationality can have on a person’s experience of being identified as a victim of trafficking in the UK. Responses to individuals and disparities in rates of recognition depending on nationality are cause for great concern. The rhetoric and the response to women who have experienced trafficking varies considerably depending upon the citizenship, residency and documentation status of the individual, particularly highlighting the differential treatment of trafficking cases of British women, European Union nationals, and third-country (non UK, non EU) nationals, the majority of whom are also asylum seekers. This differential treatment is played out in multiple ways, many of which result in women’s inability to realise procedural and substantive rights. The article examines the use of official “identification” mechanisms that place women into the administrative category of “victim”, and the central role of the asylum system in all areas of UK anti-trafficking responses.